A Community-Based Approach to Self-Prevention Practices for Periodontal Disease Among Housewives in Derawan Island - Yudha Rahina; Cicih Bhakti Purnamasari; Nisa Muthiah (Interdental Jurnal Kedokteran Gigi (IJKG), 2025)
Introduction: The prevalence of periodontal disease remains high in Indonesia. Lack of knowledge and limited access to healthcare services can lead to poor dental health status. The aim of this study is to enhance housewives' knowledge of self-prevention practices for periodontal disease on Derawan Island. Material and Methods: This study utilized a true experiment with a Randomized Pretest-Posttest Control Group Design involving 42 housewives. The intervention included knowledge enhancement using a module book and periodontal health education. Knowledge of periodontal health was assessed using questionnaires, while behavior in periodontal disease prevention was evaluated using the Oral Hygiene Index-Simplified (OHIS). The collected data were analyzed using the Wilcoxon signed-rank test and Spearman's rank correlation test. Results and Discussions: The majority of respondents had good knowledge (85,72%), while their oral hygiene was in the moderate category (54,55%). An increase in knowledge was observed in 19,05% of respondents. There was a significant difference in knowledge before and after the intervention (P<0,05). However, no significant correlation was found between knowledge and OHIS (P>0,05) Conclusion: Knowledge of periodontal disease prevention among housewives on Derawan Island has increased. Good knowledge among most housewives can serve as a foundation for independent periodontal disease prevention behaviors. This study is still ongoing to observe changes in self-prevention behavior.